Progress of N2 fixation by Ricea-Rhizobium association - Zuan, Ali Tan Kee; Ahmad Ghazali, Amir Hamzah; Baset Mia, M. A. (Springer, 2022)
Large amounts of nitrogen fertilizer are required for successful rice production, which is very costly and hazardous to the environment. The biofertilizer application is an alternative source of chemical fertilizer that can create an environment-friendly sustainable rice production system. They are microbial inoculum often used for boosting crop productivity. Recently, the application of rhizobia biofertilizer has gained prominence for a sustainable rice production system. A large body of researches has been performed to develop a suitable rhizobia biofertilizer to increase rice production. However, the success rate is not satisfactory, and this chapter discusses the progress and challenges of developing suitable biofertilizers for rice cultivation.